Preparation method of graphene-coated superfine metal composite material with high thermal stability

By growing graphene on the surface of ultrafine metal particles and completely encapsulating metal particles, the problem of grain growth of ultrafine metal materials in high temperature environments is solved, and the thermal stability and comprehensive mechanical properties of the material are significantly improved.

CN119426596APending Publication Date: 2025-02-14NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411515636.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing ultrafine crystalline metal materials are prone to grain growth under high temperature environments, resulting in poor thermal stability of the material and affecting its practical application.

Method used

By growing graphene on the surface of ultrafine metal particles, the two-dimensional structure of graphene is used to completely encapsulate metal particles, inhibit grain boundary migration and grain growth, thereby improving the thermal stability of the material.

Benefits of technology

The hardness of graphene-coated ultrafine metal composite material did not decrease after high-temperature annealing, the grain thermal stability temperature was significantly improved, and the comprehensive mechanical properties of the material were also improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphene-coated superfine metal composite material with high thermal stability. The preparation method comprises the following steps: step 1, preparing metal particles coated with organic matters; 2, the metal particles coated with the organic matter are placed in a heating furnace, H2 / Ar mixed gas is introduced, then the temperature in the heating furnace is increased to 700-1000 DEG C, CH4 / Ar mixed gas is introduced into the heating furnace to grow graphene, finally, the temperature in the heating furnace is rapidly reduced, and metal particles coated with graphene are obtained; 3, the metal particles coated with the graphene are pressed into a blocky sample; and 4, the blocky sample obtained in the step 3 is placed in a heating furnace to be subjected to vacuum annealing, and the densified graphene-coated superfine metal composite material is obtained. The method has the advantages of being easy to operate and low in cost, and the prepared graphene-coated superfine metal composite material has the advantage of being good in thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal composite material preparation methods, in particular to a method for preparing a graphene-coated ultrafine metal composite material with high thermal stability. Background Art

[0002] Metal materials are one of the important structural materials widely used in daily life and national economic construction. They play an irreplaceable role in social development and become a solid foundation for scientific and technological progress and social development. As the application environment of metal materials becomes more and more complex and demanding, single high strength or high toughness is difficult to meet the needs of special application environments. Therefore, further improving the service life of corresponding structural materials, enhancing the comprehensive mechanical properties of materials, reducing the manufacturing cost of materials, and obtaining low-cost advanced structural materials with high strength and high toughness are crucial to achieve weight reduction, energy conservation and emission reduction, and sustainable development of the economy and society.

[0003] According to the Hall-Petch theory, within a certain range of grain sizes, the yield strength of metal materials increases with the increase in the ratio of the negative half of the grain size. Based on this theory, ultrafine-grained materials are receiving more and more attention. Compared with traditional coarse-grained materials, ultrafine-grained materials have a large proportion of grain boundaries. Although the existence of these grain boundaries improves the mechanical properties of the material, it also causes the material itself to be in a metastable state. The additional Gibbs free energy remains inside the material, causing it to have a tendency to transition to an equilibrium state. This causes ultrafine-grained materials to be prone to grain growth at high temperatures or even at room temperature. This instability poses a hidden danger to the practical application of ultrafine-grained materials. Therefore, improving the thermal stability of ultrafine-grained materials is a very important aspect of developing new ultrafine-grained materials.

[0004] The methods reported so far to improve the thermal stability of ultrafine-grained metal materials can be roughly divided into two categories: (1) by introducing nanoscale low-energy interfaces to reduce the system energy, thereby improving the stability of ultrafine-grained materials. However, it is very difficult to generate three-dimensional nanocrystalline grains in pure metals where each grain boundary is in a low-energy state. Most of the research work is theoretical analysis or computer simulation, and there is relatively little experimental work; (2) adding alloying elements or second phases. Although this method can pin grain boundaries or phase boundaries, reduce the interface migration rate, and thus improve the stability of the microstructure, it may form competitive second phases including solid solutions or ordered intermetallic compounds near the stable temperature, thereby depleting grain boundary segregation and inducing grain growth.

[0005] Graphene is a two-dimensional single-layer material composed of sp2-bonded carbon atoms. It has a huge specific surface area and excellent mechanical properties. Unlike traditional second-phase particles, graphene with two-dimensional properties can theoretically completely wrap metal grains, thereby more effectively improving thermal stability. It is worth noting that even if graphene reacts with certain types of metals to form metal carbides, the newly formed product will still wrap each grain and still play a role in grain boundary segregation and inhibit grain migration. Therefore, it is of great significance to develop a method for graphene-coated ultrafine metal particles to improve thermal stability. Summary of the invention

[0006] The invention provides a method for preparing a graphene-coated ultrafine metal composite material with high thermal stability, so as to solve the problem of poor thermal stability of ultrafine-grained metal materials prepared by the prior art.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a high thermal stability graphene-coated ultrafine metal composite material comprises the following steps: Step 1, preparing metal particles coated with organic matter; Step 2, placing the organic-coated metal particles obtained in step 1 in a heating furnace, and introducing a H2 / Ar mixed gas at a flow rate of 10-800 sccm into the heating furnace at normal pressure until step 2 is completed; Next, the temperature in the heating furnace is raised to 700-1000° C., and then a CH4 / Ar mixed gas with a flow rate of 5-800 sccm is introduced into the heating furnace to grow graphene. The CH4 / Ar mixed gas is introduced for 3-60 min. Finally, the temperature in the heating furnace is rapidly lowered to obtain graphene-coated metal particles; Step 3, pressing the graphene-coated metal particles obtained in step 2 into a block sample; Step 4: placing the block sample obtained in step 3 in a heating furnace for vacuum annealing, the vacuum annealing temperature is 600-1000° C., the vacuum annealing time is 0.5-5 h, and after the vacuum annealing is completed, a densified graphene-coated ultrafine metal composite material is obtained.

[0008] In a further step 1, the organic matter is dissolved in an organic solvent to form an organic solution, and then the metal powder is added to the organic solution and stirred for 0.5-16 hours, and then the organic solution is centrifuged and dried in sequence, thereby obtaining metal particles coated with organic matter.

[0009] Furthermore, the organic matter is one or a combination of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, stearic acid, rosin, and polystyrene.

[0010] Furthermore, the organic solvent is one or a combination of isopropanol, ethanol, ethylene glycol, carbon tetrachloride, hexadecanol, and acetone.

[0011] Furthermore, the material of the metal powder is one of copper, silver and cobalt.

[0012] In the further step 2, the volume proportion of hydrogen in the introduced H2 / Ar mixed gas is 0.5-60%.

[0013] In the further step 2, the volume proportion of methane in the introduced CH4 / Ar mixed gas is 0.5-80%.

[0014] Furthermore, during the rapid cooling in step 2, the cooling rate is greater than 50°C / min.

[0015] In the present invention, micron-sized metal powder is used as raw material, and after the metal powder is uniformly mixed with organic matter containing carbon elements, high-quality graphene is grown on the particle surface of the metal powder by converting the organic material into a carbon source at high temperature. Each metal particle is wrapped by graphene grown based on a solid carbon source, which can effectively avoid the sintering and agglomeration problem of metal powder caused by the growth of a gaseous carbon source alone. The obtained graphene-coated metal particles are pressed and annealed to prepare a graphene-coated ultrafine metal composite material.

[0016] In the present invention, the presence of graphene on the surface of metal particles inhibits grain boundary migration and hinders grain growth, thereby improving the thermal stability of the metal material. Compared with the original ultrafine metal material, the graphene-coated super metal composite material prepared by the present invention has no decrease in hardness after high-temperature annealing, and the thermal stability temperature of the grains is significantly improved.

[0017] The preparation method of the present invention has the advantages of easy operation and low cost, and the prepared graphene-coated ultrafine metal composite material has the advantage of good thermal stability. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with embodiments.

[0019] Example 1 This embodiment discloses a method for preparing a graphene-coated ultrafine metal composite material with high thermal stability, comprising the following steps: Step 1: Prepare metal particles coated with organic matter, wherein the material of the metal particles is copper, and the process is as follows: The organic matter is dissolved in an organic solvent to form an organic solution, and then copper powder is added into the organic solution and stirred for 0.5-16 hours. The organic solution is then centrifuged and dried in sequence to obtain copper particles coated with the organic matter.

[0020] In this embodiment, the organic matter is one or a combination of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, stearic acid, rosin, and polystyrene. The organic solvent is one or a combination of isopropanol, ethanol, ethylene glycol, carbon tetrachloride, hexadecanol, and acetone. When the organic matter is dissolved in the solvent to form an organic solution, the mass ratio of the organic matter to the organic solvent is 1:25.

[0021] In this embodiment, the particle size of the copper powder is 1-2 μm, and the mass ratio of the copper powder to the organic solution is 1:5-20.

[0022] Step 2: preparing graphene-coated copper particles, the process is as follows: A tubular furnace is used as a heating furnace, the organic-coated copper particles obtained in step 1 are spread flat on a quartz boat, and then the quartz boat is placed in the tubular furnace, and a H2 / Ar mixed gas with a flow rate of 10-800 sccm is introduced into the tubular furnace at normal pressure until step 2 is completed; the volume proportion of hydrogen in the introduced H2 / Ar mixed gas is 0.5-60%.

[0023] Next, the temperature in the tubular furnace is raised to 700-1000° C., and then a CH4 / Ar mixed gas with a flow rate of 5-800 sccm is introduced into the tubular furnace to grow graphene. The introduction time of the CH4 / Ar mixed gas is 3-60 min; the volume proportion of methane in the introduced CH4 / Ar mixed gas is 0.5-80%.

[0024] Finally, the temperature in the tube furnace is rapidly cooled down at a rate greater than 50°C / min, thereby obtaining graphene-coated copper particles.

[0025] Step 3, pouring the graphene-coated copper particles obtained in step 2 into a powder tableting mold, and loading the powder tableting mold into a tablet press for tableting. During tableting, the tablet press is pressurized to 5-60 MPa and maintained at a pressure of 5-120 min, thereby pressing the graphene-coated copper particles into block samples.

[0026] Step 4: placing the block sample obtained in step 3 in a tubular furnace for vacuum annealing, the vacuum annealing temperature is 600-1000° C., the vacuum annealing time is 0.5-5 h, and after the vacuum annealing is completed, a densified graphene-coated ultrafine copper composite material is obtained.

[0027] In this embodiment, the prepared graphene-coated ultrafine copper composite material is vacuum annealed at different temperatures (600-1000°C), and the samples annealed at different temperatures are polished and tested for hardness, and their grain size is characterized by scanning electron microscopy. Characterization shows that the average grain size of the graphene-coated ultrafine copper composite material annealed at 600°C to 1000°C is less than 1.35 μm, and the Vickers hardness remains above 80 HV; after annealing at 700°C, the average grain size of the pure copper sample without graphene grows to 4.23 μm, and the Vickers hardness drops to 35 HV. It can be seen that the thermal stability temperature of the graphene-coated ultrafine copper composite material prepared in this embodiment is 300°C higher than that of the pure copper sample.

[0028] Example 2 This embodiment discloses a method for preparing a graphene-coated ultrafine metal composite material with high thermal stability, comprising the following steps: Step 1: Prepare metal particles coated with organic matter, wherein the material of the metal particles is silver, and the process is as follows: The organic matter is dissolved in an organic solvent to form an organic solution, and then the silver powder is added into the organic solution and stirred for 0.5-16 hours, and then the organic solution is centrifuged and dried in sequence, thereby obtaining organic-coated silver particles.

[0029] In this embodiment, the organic matter is one or a combination of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, stearic acid, rosin, and polystyrene. The organic solvent is one or a combination of isopropanol, ethanol, ethylene glycol, carbon tetrachloride, hexadecanol, and acetone. When the organic matter is dissolved in the solvent to form an organic solution, the mass ratio of the organic matter to the organic solvent is 1:25.

[0030] In this embodiment, the particle size of the silver powder is 1-2 μm, and the mass ratio of the silver powder to the organic solution is 1:5-20.

[0031] Step 2: Prepare graphene-coated silver particles, the process is as follows: A tubular furnace is used as a heating furnace, the organic-coated silver particles obtained in step 1 are spread flat on a quartz boat, and then the quartz boat is placed in the tubular furnace, and a H2 / Ar mixed gas with a flow rate of 10-800 sccm is introduced into the tubular furnace at normal pressure until step 2 is completed; the volume proportion of hydrogen in the introduced H2 / Ar mixed gas is 0.5-60%.

[0032] Next, the temperature in the tubular furnace is raised to 700-1000° C., and then a CH4 / Ar mixed gas with a flow rate of 5-800 sccm is introduced into the tubular furnace to grow graphene. The introduction time of the CH4 / Ar mixed gas is 3-60 min; the volume proportion of methane in the introduced CH4 / Ar mixed gas is 0.5-80%.

[0033] Finally, the temperature in the tube furnace is rapidly cooled down at a rate greater than 50°C / min, thereby obtaining graphene-coated silver particles.

[0034] Step 3, pouring the graphene-coated silver particles obtained in step 2 into a powder tableting mold, and loading the powder tableting mold into a tablet press for tableting. During tableting, the tablet press is pressurized to 5-60 MPa and maintained at a pressure of 5-120 min, thereby pressing the graphene-coated silver particles into a block sample.

[0035] Step 4: placing the block sample obtained in step 3 in a tubular furnace for vacuum annealing, the vacuum annealing temperature is 600-1000° C., the vacuum annealing time is 0.5-5 h, and after the vacuum annealing is completed, a densified graphene-coated ultrafine silver composite material is obtained.

[0036] In this embodiment, the graphene-coated ultrafine silver composite material is vacuum annealed at different temperatures (600-900°C), and the samples annealed at different temperatures are polished and tested for hardness, and the grain size is characterized by a scanning electron microscope. Characterization shows that the average grain size of the graphene-coated ultrafine silver composite material annealed at 600°C to 900°C is less than 1.08 μm, and the Vickers hardness remains above 74 HV; after annealing at 600 degrees, the average grain size of the pure silver sample without graphene grows to 2.96 μm, and the Vickers hardness drops to 42 HV. It can be seen that the thermal stability temperature of the graphene-coated ultrafine silver composite material prepared in this embodiment is 300°C higher than that of the pure silver sample.

[0037] Example 3 This embodiment discloses a method for preparing a graphene-coated ultrafine metal composite material with high thermal stability, comprising the following steps: Step 1: Prepare metal particles coated with organic matter, wherein the material of the metal particles is cobalt, and the process is as follows: The organic matter is dissolved in an organic solvent to form an organic solution, and then cobalt powder is added to the organic solution and stirred for 0.5-16 hours, and then the organic solution is centrifuged and dried in sequence to obtain organic-coated cobalt particles.

[0038] In this embodiment, the organic matter is one or a combination of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, stearic acid, rosin, and polystyrene. The organic solvent is one or a combination of isopropanol, ethanol, ethylene glycol, carbon tetrachloride, hexadecanol, and acetone. When the organic matter is dissolved in the solvent to form an organic solution, the mass ratio of the organic matter to the organic solvent is 1:25.

[0039] In this embodiment, the particle size of the cobalt powder is 1-2 μm, and the mass ratio of the cobalt powder to the organic solution is 1:5-20.

[0040] Step 2: preparing graphene-coated cobalt particles, the process is as follows: A tubular furnace is used as a heating furnace, the organic-coated cobalt particles obtained in step 1 are spread flat on a quartz boat, and then the quartz boat is placed in the tubular furnace, and a H2 / Ar mixed gas with a flow rate of 10-800 sccm is introduced into the tubular furnace at normal pressure until step 2 is completed; the volume proportion of hydrogen in the introduced H2 / Ar mixed gas is 0.5-60%.

[0041] Next, the temperature in the tubular furnace is raised to 700-1000° C., and then a CH4 / Ar mixed gas with a flow rate of 5-800 sccm is introduced into the tubular furnace to grow graphene. The introduction time of the CH4 / Ar mixed gas is 3-60 min; the volume proportion of methane in the introduced CH4 / Ar mixed gas is 0.5-80%.

[0042] Finally, the temperature in the tubular furnace is rapidly cooled at a rate greater than 50°C / min, thereby obtaining graphene-coated cobalt particles.

[0043] Step 3, pouring the graphene-coated cobalt particles obtained in step 2 into a powder tableting mold, and loading the powder tableting mold into a tablet press for tableting. During tableting, the tablet press is pressurized to 5-60 MPa and maintained at a pressure of 5-120 min, thereby pressing the graphene-coated cobalt particles into block samples.

[0044] Step 4: placing the block sample obtained in step 3 in a tubular furnace for vacuum annealing, the vacuum annealing temperature is 600-1000° C., the vacuum annealing time is 0.5-5 h, and after the vacuum annealing is completed, a densified graphene-coated ultrafine cobalt composite material is obtained.

[0045] In this embodiment, the graphene-coated ultrafine cobalt composite material is vacuum annealed at different temperatures (600-1000°C), and the samples annealed at different temperatures are polished and tested for hardness, and their grain size is characterized by scanning electron microscopy. Characterization shows that the average grain size of the graphene-coated ultrafine cobalt composite material annealed at 600°C to 1000°C is less than 0.78 μm, and the Vickers hardness remains above 225 HV; after annealing at 800 degrees, the average grain size of the pure cobalt sample without graphene composite grows to 1.50 μm, and the Vickers hardness drops to 170 HV. It can be seen that the thermal stability temperature of the graphene-coated ultrafine cobalt composite material prepared in this embodiment is 200°C higher than that of the pure cobalt sample.

[0046] The above describes the embodiments of the present invention in detail. The embodiments described in the present invention are only descriptions of the preferred embodiments of the present invention, and do not limit the concept and scope of the present invention. The various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. As long as such combination does not violate the concept of the present invention, it should also be regarded as the content disclosed in the present disclosure. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations.

[0047] The present invention is not limited to the specific details of the above-mentioned embodiments. Within the technical concept of the present invention and without departing from the design concept of the present invention, various modifications and improvements made to the technical solution of the present invention by technical personnel in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have been fully recorded in the claims.

Claims

1. A method for preparing a high thermal stability graphene-coated ultrafine metal composite material, characterized in that: The following steps are involved: Step 1, preparing metal particles coated with organic matter; Step 2, placing the organic-coated metal particles obtained in step 1 in a heating furnace, and introducing a H2 / Ar mixed gas at a flow rate of 10-800 sccm into the heating furnace at normal pressure until step 2 is completed; Next, the temperature in the heating furnace is raised to 700-1000° C., and then a CH4 / Ar mixed gas with a flow rate of 5-800 sccm is introduced into the heating furnace to grow graphene. The CH4 / Ar mixed gas is introduced for 3-60 min. Finally, the temperature in the heating furnace is rapidly lowered to obtain graphene-coated metal particles; Step 3, pressing the graphene-coated metal particles obtained in step 2 into a block sample; Step 4: placing the block sample obtained in step 3 in a heating furnace for vacuum annealing, the vacuum annealing temperature is 600-1000° C., the vacuum annealing time is 0.5-5 h, and after the vacuum annealing is completed, a densified graphene-coated ultrafine metal composite material is obtained.

2. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 1, characterized in that: In step 1, the organic matter is dissolved in an organic solvent to form an organic solution, and then the metal powder is added to the organic solution and stirred for 0.5-16 hours, and then the organic solution is centrifuged and dried in sequence to obtain metal particles coated with organic matter.

3. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 2, characterized in that: The organic matter is one or a combination of polyacrylonitrile, polyvinyl pyrrolidone, polymethyl methacrylate, stearic acid, rosin, and polystyrene.

4. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 2, characterized in that: The organic solvent is one or a combination of isopropanol, ethanol, ethylene glycol, carbon tetrachloride, hexadecanol, and acetone.

5. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 2, characterized in that: The material of the metal powder is one of copper, silver and cobalt.

6. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 1, characterized in that: In step 2, the volume proportion of hydrogen in the H2 / Ar mixed gas introduced is 0.5-60%.

7. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 1, characterized in that: In step 2, the volume proportion of methane in the CH4 / Ar mixed gas introduced is 0.5-80%.

8. The method for preparing a high thermal stability graphene-coated ultrafine metal composite material according to claim 1, characterized in that: When the temperature is rapidly cooled in step 2, the cooling rate is greater than 50°C / min.